Changes in Empathy in Patients With Chronic Low Back Pain: A Structural–Functional Magnetic Resonance Imaging Study - Ma, Junqin; Wang, Xianglong; Qiu, Qing; Zhan, Hongrui; Wu, Wen (Frontiers in Human Neuroscience, 2020)
Objective: Many pieces of research have focused on pain within individuals, but little attention has been paid to whether pain can change an individual's empathic ability and affect social relationships. The purpose of this study is to explore how chronic low back pain changes empathy. Methods: Twenty-four chronic low back pain patients and 22 healthy controls were recruited. We set up an experimental pain-exposed model for each healthy subject. All subjects received a painful-empathic magnetic resonance scan. After the scan, all subjects rated the pain intensity and multiple empathy-related indicators. The clinical assessment scale was the 20 items Basic Empathy Scale in Adults. Result: The chronic low back pain patients reported lower scores on the total scores of BES-A, the subscale scores of emotional disconnection and cognitive empathy, and the discomfort rating. The fMRI results in the chronic low back pain patients showed that there were multiple abnormal brain pathways centred on the anterior insula. The DTI results in the chronic low back pain patients showed that there were reduced fractional anisotropy values in the corpus callosum, bilateral anterior thalamic radiation, right posterior thalamic radiation, right superior longitudinal fasciculus, and left anterior corona radiate. Conclusion: Our study found that patients with chronic low back pain have impaired empathy ability. The abnormal functional connectivity of multiple brain networks, multiple damaged white matter tracts, and the lower behavioural scores in chronic low back pain patients supported our findings.